'Fantasy of Fusion' as a Response to Trauma: European Leaders and the Origins of the Eurozone Crisis. Issue 7 (July 2016) - Stein, Mark
In this paper I explore a new approach to the understanding of trauma. I call into question the widely held assumption that trauma tends to engender feelings of dejection, lethargy and helplessness. Instead, I argue that it can lead to a quite different, active and over-optimistic response that involves an attempt at fusion with those who have inflicted, or might yet inflict, trauma. Drawing on concepts from psychoanalysis, I introduce the term 'fantasy of fusion' to encapsulate this idea. This concept is illustrated by an examination of the role of European leaders in the crucial decision to launch the single currency, and an exploration of its ramifications in creating the conditions for the eurozone crisis. The contribution of this paper is threefold. First, calling into question the assumption that trauma leads to feelings of helplessness, this paper introduces and develops the novel idea of 'fantasy of fusion'. Second, it sheds further light on the challenges of leadership. Third, it provides a new deep structure explanation for the origins of the eurozone crisis.